(untitled) (Research, Society and Development, 2020)
Studies on genetic diversity of cacti are important to elucidate evolutionary events and ecological characteristics of populations vulnerable to genetic erosion. The objective of this study was to evaluate the genetic diversity among individuals of Pilosocereus catingicola subsp. salvadorensis occurring in three populations located in the Caatinga do Agreste region of Paraiba, using RAPD markers. For the extraction of DNA, tissues of the parenchyma and cladodium of the stem of the individuals were used by the 2% CTAB method and amplified using 05 primers. The obtained marks were converted into a binary matrix, from which the matrix of genetic dissimilarity was constructed using the arithmetic complement of the Jaccard coefficient and the construction of the dendrogram, by the UPGMA method. All markers tested amplified, being 82.4% polymorphic locus and 10.6% monomorphic for the Arara population; 84.4% polymorphic and 15.6% monomorphic for the Areial population, the Boa Vista population did not show monomorphism, resulting in 100% polymorphism. The averages of heterosigose observed (0.372, 0.492 and 0.135) show that there are genetic divergences within the populations. The primers used were effective in identifying polymorphism in the species. The populations evaluated in this study showed high genetic diversity, both within and between the population, originating fifteen groups among the 120 individuals from the UPGMA hierarchical grouping analysis, and it was possible to discriminate the populations.